Antimicrobial Activity of Various Extracts from Different Parts of Amaranthus mangostanus - Zhang, Ya; Su, Pin; Huang, Huang; Liu, Shuangqing; Liao, Xiaolan (Asian Journal of Chemistry, 2013)
Amaranthus mangostanus is a green vegetable which is also used as sudorific, febrifuge, emollient, lactogogue and a specific treatment for colic. This study was aimed to determine antibacterial and antifungal activities of the methanol, dichloromethane, petroleum ether and ethyl acetate extracts from different parts of A. mangostanus against microbes that cause plant or human diseases and food contamination. At concentrations ranging from 40-100 mg/mL, ethyl acetate extracts from leaves and stems exhibited concentration-dependent inhibition against Pseudomonas solanacearum Smith, Acidovorax avenae subsp. A. Citrulli, Rhizoctonia solani, Colletotrichum capsici (syd.) Butl, Pseudomonas aeruginosa, Bacillus cereus and Escherichia coli, but not Magnaporthe grisea, Alternaria alternata Keissler, Phytophtora parasitica var. nicotianae Tucker and Fusarium graminearum Sehw., with MIC values of 519-713 and 463-697 mg/mL, respectively, whereas the ethyl acetate extract from roots only showed antibacterial activity against P. solanacearum Smith with an MIC of 815 mg/mL. Ethyl acetate extracts from leaves and stems also showed inhibitory effect on the fungus R. solani, with MICs of 686 and 734 mg/mL, respectively. Consequently the information on the antimicrobial functions of the extracts can shed light on the discovery of natural products for management of plant and human infectious diseases.